Perancangan Program Sistem Smart Gate Berbasis Indikator Suhu dan Wastafel Otomatis - Anam, Rofiul; Arifin, Samsul (Institut Tekonologi dan Binisi Asia Malang, 2024)
Checking human body temperature and washing hands are very important in implementing health protocols in this era of the COVID-19 pandemic, especially on the path or entering a building. In general, these two things are still done conventionally so that it is still possible to have excessive direct physical contact with temperature checkers and hand washing sinks. So in this study, a tool is designed to be used to check temperature and wash hands automatically which later will be an indicator to open a gate or automatic portal as a path or entrance to a building/building. It is hoped that this tool will be able to minimize direct physical contact that will be caused by the current conventional system so as to minimize the risk of covid 19 transmission. This tool uses a temperature sensor gy906/mlx 90614 as a non-contact temperature sensor and uses ultrasonic as an object distance detection, and also uses an actuator DC motor as a driver to open or close the gate.